PENDAFTARAN TANAH SISTEMATIS LENGKAP DI KECAMATAN CILINCING JAKARTA UTARA - Shafa Salsabila; Endang Suparsetyani (Fakultas Hukum Universitas Trisakti, 2021)
Complete Systematic Land Registration is a registration activity carried out simultaneously for all objects of land registration in all village areas. The problem: is the implementation of PTSL in Cilincing District, North Jakarta appropriate or not according to the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency No. 6 of 2018? And what are the obstacles in implementing PTSL in Cilincing District, North Jakata? how to overcome the problems that become obstacles to the implementation of PTSL in Cilincing District, North Jakarta? The research is normative, descriptive in nature, the data and use primary and secondary data, analyzed qualitatively, drawing conclusions using deductive logic. Research results, discussion and conclusions; The implementation of PTSL in Cilincing District, North Jakarta is in accordance with Article 4 Paragraph (4) Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency No. 6 of 2018. Obstacles in its implementation are the lack of active public awareness, data collection, difficult parties found, measurement of land parcels, one object of land parcels claimed by two parties, submission of certificates, limited counseling and division of work time during the pandemic.